Marine Physiology Down East: The Story of the Mt. Desert Island Biological Laboratory - Evans, David H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2015)
This volume offers a comprehensive history of the Mount Desert Island Biological Laboratory (MDIBL), one of the major marine laboratories in the United States and a leader in using marine organisms to study fundamental physiological concepts. Beginning with its founding as the Harpswell Laboratory of Tufts University in 1898, David H. Evans follows its evolution from a teaching facility to a research center for distinguished renal and epithelial physiologists. He also describes how it became the site of major advances in cytokinesis, regeneration, cardiac and vascular physiology, hepatic physiology, endocrinology and toxicology, as well as studies of the comparative physiology of marine organisms. Fundamental physiological concepts in the context of the discoveries made at the MDIBL are explained, and the social and administrative history of this renowned facility is described.
Beginnings at Harpswell, Maine -- Early Years on Mount Desert Island: The First Generation -- The Second Generation: MDIBL in the 1930s -- Wartime and the Early Postwar Years: Bust and Boom at the MDIBL -- MDIBL in the Postwar: The Third Generation -- Mid Century: The Third Generation Redux -- Year-Round Operation: The First Attempt -- Research in the Seventies: The Fourth Generation -- MDIBL in the 1980s: Doors Close, Doors Open -- Research in the 1980s: The Fifth Generation -- The Centennial Decade of the MDIBL -- Research in the 1990s: Molecular Biology Comes to the MDIBL -- The MDIBL in the Early 21st Century: A New Beginning -- Research in the Early 21st Century: The Year-Round Research Program Comes of Age.
Keywords: Medicine; History; Human physiology; Animal physiology; Biomedicine; Human Physiology; Animal Physiology; History of Science; Electronic books